Pressure Drop in Horizontal Two-Phase Flow - Ibrahim, S. S.; Abdulkareem, L. A. (Engineering, Technology & Applied Science Research, 2022)
In an artificial environment, the most important key in the process equipment design is determining gas-liquid two-phase flow frictional pressure drop of pipes. To achieve this, an experimental investigation was carried out in this study to analyze the pressure drops of air-water two-phase flow in a 30mm internal diameter horizontal pipe with a length of 6m at different flow conditions. The study was carried out at 20Co using tap water and air. To cover the slug flow pattern, the volumetric flow rate of water varied from 30 to 80 LPM, and the volumetric flow rate of air from 40 to 200 LPM. Pressure transmitters were used to measure pressure at four different points along the test section, each 2m apart. The results of the experiments were compared to 8 models using 3 distinct methods: Mean Absolute Percentage Error (MAPE), Relative Performance Factor (RPF), and the percentage of data included in the range of the 30% error band. All methods produced similar results, with the Sun-Mishima model being the most accurate.